Exosomic microRNAs in the Tumor Microenvironment - Neviani, Paolo; Fabbri, Muller (Frontiers in Medicine, 2015)
Dissecting the cross talk between tumor cells and tumor microenvironment is quickly becoming the new frontier in cancer research. It is now widely accepted that cancer cells can exert a profound influence over their surroundings, by changing the microenvironment from a normal to a tumor-supportive state that allows for sustained tumor-growth, invasion and drug-resistance. Extracellular vesicles, especially exosomes, are recognized as a new category of intercellular communicator and they are emerging as of primary importance in controlling the interplay between the tumor and its environment. Exosomes derived from cancer cells or from cells of the tumor microenvironment allow for the horizontal transfer of information by virtue of their cargo, made of functional proteins and nucleic acids that are specifically sorted and loaded in exosomes during their biogenesis. In this review we will discuss the current knowledge regarding the role invested by microRNAs, a family of short non-coding RNAs frequently deregulated in malignancies and present in exosomes, in shaping the microenvironment in a cancer-dependent manner.